Model creative dance sebagai panduan penciptaan karya tari anak - Sari, Dyan Indah Purnama; Syefriani, Syefriani; Rachmawati, Putri (Universitas Sarjanawiyata Tamansiswa, 2024)
Many teachers in schools who do not have a basic dancer become a scourge when teaching dance material, this is due to the lack of knowledge of teachers regarding how to create dance works easily. Many models of approach to creating without having to have a basic dance but still understand the basics of creating dance, one of the models used to develop the ability to create dance in children is creative dance. creative dance models prioritize the process of concept analysis, motion analysis, motion exploration, imagination, and free expression without being bound by strict formal dance techniques but with the right intent and purpose. The creative dance model is a structured step in learning dance to create a dance work creatively and not difficult. This research aims to describe the creative dance model as a guide in the creation of children's dance works for students of Fine Arts Education at Sarjanawiyata Tamansiswa University. This type of qualitative research explores the theories underlying creative dance and its implementation in the process of creating children's dance works through observation, interviews, and documentation. Primary data sources in this research are students of Fine Arts Education, Sarjanawiyata Tamansiswa University, totaling 11 active students. The research findings are in the form of guidelines for creating children's dance works consisting of analysis, stimulus response, exploration, construction/composition, reflection, presentation. It is hoped that the results of this study will contribute to the development of children's dance education, especially teachers without a dance background such as Fine Arts Education students, can create dance works that contain educational values, creativity, and art that can be accepted by children.